Optimalisasi Legalitas UMKM Perempuan melalui Program Peningkatan Kapasitas UMKM CSR Bank SUMUT di Kota Medan - Amilia Hasbullah; Ahmad Hermanto; Ihsan Satrya Azhar; Mukhlis Mukhlis (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a key role in the present-day economy of the nation. One aspect of enhancing the capabilities of micro, small, and medium enterprises (UMKM) is ensuring their compliance with regulatory requirements. The first phase involved the legal registration of the NIB (National Identification Number for Businesses) to facilitate the professional monitoring of commercial competitiveness for micro, small, and medium enterprises (UMKM). In accordance with the significance of enhancing the capacity of micro, small, and medium enterprises (UMKM) in the City of Medan, CSR Bank SUMUT, in collaboration with academic professionals from Krisnadwipayana Univeristy, has initiated a program aimed at providing assistance, socialization, and support for the establishment of NIB. This program forms part of the Women's UMKM Capacity Enhancement Program, which is being implemented in the city of Medan. Through socialization and direct guidance to Women SMEs in Medan, it has contributed to an enhanced comprehension among them about the importance legal aspects of their businesses.